Адсорбція катіонних барвників на соломі ячменю, модифікованій лимонною кислотою: кінетичні, рівноважні та термодинамічні дослідження - Soldatkina, L. M.; Yanar, M. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2022)
The adsorption performance of cationic dyes (methylene blue and malachite green) on barley straw modified by citric acid has been studied. Barley straw modified by citric acid is a low-cost and eco-friendly adsorbent, however the effectiveness of the adsorbent towards cationic dyes have not yet been examined. Accordingly, kinetic, equilibrium, and thermodynamic aspects of the cationic dyes adsorption from aqueous solution were studied in order to evaluate the citric acid modified barley straw efficiency. The modified barley straw was characterized versus unmodified matter using Fourier Transform Infrared spectroscopy (FT-IR). FT-IR analysis showed that modification of barley straw using citric acid allowed us to increase the number of carboxyl groups on the straw surface. Adsorption studies were conducted on a batch process, to study the effects of contact time, concentration of cationic dyes, and temperature. The results of kinetic experiments showed that adsorption process attained equilibrium within 120 and 90 min for methylene blue and malachite green, respectively, and equilibrium time for both the cationic dyes was temperature independent. The adsorption kinetics of the cationic dyes was well described by the pseudo-second order model. The equilibrium data are analyzed by the Freundlich, Langmuir, and Temkin isotherms. The experimental data of adsorption indicated more conformity with the Langmuir isotherm model for methylene blue and malachite green adsorption on the modified straw. Furthermore, the thermodynamic parameters calculated at 293–333 K showed that the adsorption of methylene blue and malachite green on the modified straw was endothermic. Negative results of ?Go-values (between ?32.1 and ?24.6 kJ mol?1) indicated that the adsorption process was spontaneous at all the tested temperatures. Desorption of methylene blue and malachite green from the exhausted adsorbent was estimated using water and aqueous solutions of hydrochloric and acetic acids. Desorption efficiency follows the order: HCl > CH3COOH > H2O. The study has revealed that citric acid modified barley straw is an effective adsorbent and can be used as an alternative for more costly adsorbents used for cationic dyes removal from wastewater.